The EFL Students' Narrative Paragraph Writing of The Second Semester Students of State Institute of Islamic Studies (IAIN) Samarinda: A Syntactic Analysis - La Ode Sanu (Script Journal: Journal of Linguistics and English Teaching, 2016)
AbstractThis study concerned on the EFL students' ability and analyzed the sentence patterns of syntax on the narrative paragraph writing. The QUANT-QUAL of mixed methods design was used in this study. The quantitative data gathered from the test of narrative paragraph writing by involving 30 EFL students of IAIN Samarinda. The qualitative data gathered from the 10 selected documents of narratibe paragraph writing that met the criteria. The findings shoed that the EFL students' ability of narrative paragraph was categorized excellent (80.33). The highest ablity was the writing aspect of organization (86.65%) followed by vocabulary (84.00%), content (83.33%), mechanics (78.60%), and language use (69.08%). The sentence patterns of syntax found on the EFL students' narrative paragraph writing; its verbs were followed by direct object, infinitive, pronoun, present participle, adverbial phrase, that-clause, conjunctive-clause, gerund, direct object-preposition-prepositional object, complement of distance and time, verb alone, predicative and preposition-prepositional object.Keywords: Writing, Narrative Paragraph, and Sentence Patterns of Syntax